(untitled) (Bioscience Journal, 2018)
In this study, we propose a new two-dimensional graphical representation of DNA sequence based on a choice of four horizon lines. The 2D representation is constructed in a probabilistic framework. Following the new approach, we perform the similarity analysis among coding sequences of the first exon of beta-globin gene from eleven species. Our results coincide with current biological analyses. We also compare our method with some existing DNA sequence comparison algorithms and find that ours is more intuitive and effective.